Improving Writing Skill for Islamic Education Teacher - Atika, Faizah Nur (International Conference of Moslem Society, 2019)
A teacher should able to write as supporting element in learning activities implementation. Moreover, teachers also need to do research to improve the professionalism as a teacher. But right now, the culture of writing scientific papers among teachers remains low. Many efforts have been made by government to encourage the spirit of the teacher in writing as like training, but it was not enough if they had done the training but do not directly apply, then training is something useless. So, they need a habituation to write as early as possible before being a teacher as performed by An Najah Islamic Boarding School for Higher Student Purwokerto. They will be accustomed to writing as early as they can. This research can be categorized as field research while the strategy is cross sectional study case. The object are all of activity which belong to writing skill improvement there while the subjects are santri (student) and ustadz (teacher). The technic of collecting data uses observation, interview, and documentation and used Miles and Huberman data analysis methods. This study shows that there are two programs for improving writing skill of Islamic Education santri, namely main program and supported program.